Urologic co‐morbidities associated with sacrococcygeal teratoma and a rational plan for urologic surveillance. Issue 10 (17th June 2013) - Cost, Nicholas G.; Geller, James I.; Le, Louis D.; Crombleholme, Timothy M.; Keswani, Sundeep G.; Lim, Foong‐Yen; Alam, Shumyle
ABSTRACT Background Sacrococcygeal teratoma (SCT) is one of the most common neonatal and fetal tumors. SCT pelvic mass effect and the need for aggressive surgical resection, create potential for urologic co‐morbidity. We reviewed our experience with SCTs and propose a rational plan for urologic surveillance. Methods We retrospectively reviewed all patients with SCT evaluated at our institution from 2004 to 2011. We collected data on the need for reconstructive surgery related to the urologic co‐morbidity, the time to detection of urologic co‐morbidity, and length of follow‐up. Results We identified 28 patients evaluated during the study period with a median follow‐up of 3.1 year (range 0.14–13.4). The Altman classifications were—type I: 7 (25%), II: 15 (53.6%), and III: 6 (21.4%). Eighteen (64.3%) patients had an associated urologic co‐morbidity: 12 (42.9%) patients had hydronephrosis, VUR—10 (35.7%), NGB—13 (46.4%), and 4 (14.3%) developed ≥CKD2. When comparing the patients according to Altman classification, there was a trend towards more urologic co‐morbidity in patients with increasing pelvic involvement, P = 0.06. Eleven patients (39.3%) had delayed urologic evaluation and five (17.9%) required reconstructive urologic surgery. In comparing these groups, 4 of 11 (36.4%) undergoing delayed urologic evaluation progressed to reconstruction, as opposed to only one of 17 (5.7%) with urologic evaluation within first year of life (P‐value = 0.06). Conclusion Urologic co‐morbidities are common in children with SCT and appear most common in patients with more pelvic tumor involvement (≥Altman II). A risk‐adapted approach to urologic surveillance is proposed. Pediatr Blood Cancer 2013;60:1626–1629. © 2013 Wiley Periodicals, Inc.